HOW IS AI SHAPING THE FUTURE OF WORK? EMPOWERING EMPLOYEES, NOT REPLACING THEM - PETRE, Anamaria; RAȚIU, Patricia; OSOIAN, Codruța (Studia Universitatis Babeș-Bolyai Oeconomica, 2024)
In the modern business world, AI is revolutionizing HR departments around the globe and is becoming an essential part of human resource management. In this paper we explore the role of AI in Human Resource Management and how it can help organizations to remain competitive and efficient, while improving employee empowerment and engagement. We conducted quantitative research involving employees and HR professionals from various sectors in Romania to explore their perceptions of AI implementation in the workplace. The data explores the extent to which AI chatbots can empower employees and improve their efficiency. Additionally, we analyze employees' perceptions regarding the possibility of being replaced by AI, offering insights into their concerns about job displacement alongside the opportunities AI presents for job enhancement. The research findings reveal a strong positive correlation between favorable perceptions of AI and increased empowerment, while concerns about job displacement negatively affect empowerment. The study’s conclusions have significant implications for HR professionals, who can use AI tools to maximize and enhance organizational performance. Moreover, to satisfy the demands of the workforce of the future, our research also emphasizes how important it is for HR experts to integrate technology advancements into their HR strategy. JEL classification: O33; M12; M15; J24